International political economy of exchange rates: a case study of the Renminbi based on the debate between China and the United States - Zhang, Jingchun (2008)
There is no ideal formula for the determination of the foreign exchange rates (FX rates) of various currencies in international economics. The FX rate of each country is determined by the dynamic interaction of various economic and political factors at both the national and international levels.